Processi e pratiche di integrazione di rom e sinti tra famiglia, scuola e altre agenzie educative extrascolastiche - Cerrocchi, Laura; D’Antone, Alessandro; Vecchia, Roberta (Rivista Italiana di Educazione Familiare, 2015)
This paper refers to the multicultural society in regard to a pedagogical awareness and planning. This planning aims to design an integration which could overshoot the extreme opposites of separatism and social absorption, avoiding chances of deculturation as well. The Rom and Sinti integration will be discussed both on the basis of the specific legislation on the immigration field, and of social and cultural characteristics of these communities (with particular reference to family structures, language and work). The analysis of a qualitative inquiry allows to research about the contradiction and coherence factors within the field of primary and secondary socialization, of cultural transmission and relations, in regard to educational contexts within or outside school, to parents and teachers and educators. The point of view is lifelong and lifewide education through an integrated educational system.